A Comparison Study for The Performance of Polyethersulfone Ultrafiltration Mixed Matrix Membranes in The Removal of Heavy Metal Ions from Aqueous Solutions - Abdulameer, Haider Nezar; Al-Jubouri, Sama M. (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
Polyethersulfone (PES) ultrafiltration membrane blending NaX zeolite crystals as a hydrophilic additive was examined for zinc (II) and lead ions Pb (II) removal from aqueous solutions. The effect of NaX zeolite content on the permeation flux and removal efficiency was studied. The results showed that adding zeolite to the polymer matrix enhanced the permeation flux. The permeation flux of all the zeolite/PES matrix membranes was higher than the pristine membrane. No significant improvement was observed in the removal of Zn (II) ions using all prepared membranes as the removal percentage did not raise above 29.2%. However, the removal percentage of Pb (II) ions was enhanced to 97% using a membrane containing 0.9%wt. zeolite. Also, it was found that this membrane has a higher ion exchange capacity than the other prepared membranes. Two isotherm models (Langmuir model, and Freundlich model) were employed in the analysis of the ion exchange equilibrium data. The experimental data best fitted the Langmuir model with R2 of 0.889 than the Freundlich model.